2021
DOI: 10.3390/horticulturae7020028
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fertigation Management on the Quality of Organic Legumes Grown in Protected Cultivation

Abstract: Appropriate fertigation management plays an important role in increasing crop quality and economizing water. The objective of the study was to determine the effects of two fertigation treatments, normal (T100) and 50% sustained deficit (T50), on the physico-chemical quality of legumes. The determinations were performed on the edible parts of peas, French beans and mangetout. The trials were conducted in a protected cultivation certified organic farm. The response of legumes to the treatments varied between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Ref. [54] showed that French bean plants' yield was severely reduced when fertigation was reduced by half (50%).…”
Section: Pod Yieldmentioning
confidence: 99%
“…Ref. [54] showed that French bean plants' yield was severely reduced when fertigation was reduced by half (50%).…”
Section: Pod Yieldmentioning
confidence: 99%
“…The effect of environment conditions (temperature, rainfall, altitude, soil types, hail) [5][6][7][8][9], nutritional strategies [5,6,[10][11][12][13][14], water (stress, salinity) [5,8,12,15], container substrate of cultivation [16] on yield, yield traits and quality were analyzed in different crops in an open field [8,9,13,14,17] and greenhouses [5][6][7][10][11][12]15,16].…”
Section: Special Issue Overviewmentioning
confidence: 99%
“…Different innovative strategies were presented that included protected structures, container type, cultivation techniques [5,10,16], symbiotic relationships [6,7], fertigation strategies [10] new agricultural management technologies (remote sensing, smartphone) [11] novel hybrids for breeding [12] spraying of Gibberellic acid [17], water supplies [8,15] and substrate [16] cover crops management [13] and stand reduction [9].…”
Section: Special Issue Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also revealed the nutritional potential of mangetout, not only for its protein content but also for its content of total soluble solids and antioxidant compounds such as polyphenols, ascorbic acid, fiber, phytoprostanes and phytofurans [12][13][14].…”
Section: Introductionmentioning
confidence: 99%